1997
DOI: 10.1161/01.res.81.6.963
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate-Dependent Inhibition of Transendothelial Migration and Chemotaxis of Human Peripheral Blood Neutrophils by Pravastatin

Abstract: Pravastatin, a hydrophilic inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase, has been reported to beneficially affect atherogenesis, plaque stability, and transient myocardial ischemia in significant coronary artery disease by influencing lipid metabolism and by intracellular signaling via mevalonate pathway products other than cholesterol. Leukocytes are implicated to play a pathophysiological role in these events. We were interested in finding out whether pravastatin could affect transendothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 36 publications
7
54
0
Order By: Relevance
“…While a reduction in LDL-cholesterol was observed in many of these studies, it is now considered that statins also mediate pleiotropic antiatherogenic effects that are independent of their effects on lipoproteins, and that this action may contribute to their efficacy in reducing cardiovascular events. Indeed, HMGCoA reductase inhibitors have been shown to attenuate, although not in the context of diabetes, many of the stages critical to atherosclerotic plaque development including monocyte chemotaxis [13], neutrophil-endothelial cell interaction [13], smooth muscle cell apoptosis [14], migration [15] and proliferation [16], as well as plaque stability [17].…”
Section: Introductionmentioning
confidence: 99%
“…While a reduction in LDL-cholesterol was observed in many of these studies, it is now considered that statins also mediate pleiotropic antiatherogenic effects that are independent of their effects on lipoproteins, and that this action may contribute to their efficacy in reducing cardiovascular events. Indeed, HMGCoA reductase inhibitors have been shown to attenuate, although not in the context of diabetes, many of the stages critical to atherosclerotic plaque development including monocyte chemotaxis [13], neutrophil-endothelial cell interaction [13], smooth muscle cell apoptosis [14], migration [15] and proliferation [16], as well as plaque stability [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent reports suggested that neutrophils were occasionally found in disrupted plaques [11], and myeloperoxidase (MPO), the enzyme of leukocytes (including neutrophils) which promotes oxidation of lipoproteins, was present in atherosclerotic plaques [12]. These observations support the importance of neutrophil transendothelial migration in the development and disruption of atherosclerotic plaques [13]. Therefore, we focused on the correlation between hyperinsulinaemia and neutrophil transendothelial migration.…”
mentioning
confidence: 57%
“…In addition, endothelial migration of PMN obtained from diabetic patients with hyperinsulinaemia was also increased compared with that from healthy subjects. The PMN transendothelial migration enhanced by high insulin might account for the high incidence of atherosclerotic diseases such as AMI and stroke in patients with diabetes, because PMN transendothelial migration seems to contribute to the formation of atherosclerotic plaques and their disruption [4,13]. There is growing evidence supporting a close relation between atherosclerosis and PMN activation and migration [11,12,22,23,24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HMG-CoA reductase inhibitors such as pravastatin have been shown to inhibit chemotactic migration of monocytes (17) and neutrophils (18) in vitro. Treatment with pravastatin has been shown to reduce the number of monocytes infiltrated into atherosclerotic plaques (19,20) and to reduce metalloproteinase activity (21,22).…”
Section: Discussionmentioning
confidence: 99%